Mars or Mercury? The geopolitics of international currency choice. (4th July 2019) - Eichengreen, Barry; Mehl, Arnaud; Chiţu, Livia
Summary: We assess the role of economic and security considerations in the currency composition of international reserves. We contrast the 'Mercury hypothesis' that currency choice is governed by pecuniary factors familiar to the literature, such as economic size and credibility of major reserve currency issuers, against the 'Mars hypothesis' that this depends on geopolitical factors. Using data on foreign reserves of 19 countries before World War I, for which the currency composition of reserves is known and security alliances proliferated, our results lend support to both hypotheses. We find that military alliances boost the share of a currency in the partner's foreign reserve holdings by about 30 percentage points. These findings speak to the implications of possible US disengagement from global geopolitical affairs. In a hypothetical scenario where the United States withdraws from the world, our estimates suggest that long-term US interest rates could rise by as much as 80 basis points, assuming that the composition of global reserves changes but their level does not.